THE USE OF MIND MAPPING TECHNIQUE TO IMPROVE STUDENTS’ READING COMPREHENSION: A STUDY CONDUCTED AT SMP NEGERI 4 TOULUAAN - Stovan Joseph Mokosolang; Nihta Liando; Rinny Rorimpandey (Fakultas Bahasa dan Seni, Universitas Negeri Manado, 2022)
The research intends to find out whether or not mind mapping technique can improve students’ reading comprehension. The study is a pre-experimental design using one group pre-test and post-test design. The research is conducted at SMP Negeri 4 Touluaan and the subject of the study is twenty six students. To collect the data, the writers use an objective test in the form of multiple choice consisted of 10 numbers. Pre-test is given before the treatment. After treatment the students are given post-test. The mean score of the pre-test is 4.23 and the standard deviation is 1.34. Meanwhile, the mean score of post-test is 6.96 and the standard deviation is 1.09. It could be said that the result of post-test is much better or higher than those of pre-test. So, it is concluded that mind mapping technique is effective to be used in improving students’ reading comprehension. Teachers of English at junior high school are recommended to use mind technique in teaching reading comprehension to help the students improve understanding of a reading text and make them active in reading activities.